2012
DOI: 10.1021/ie202325p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Adsorption on Retention of Structure and Surface Area of Metal–Organic Frameworks

Abstract: This work presents an experimental investigation of water adsorption in metal−organic frameworks (MOFs) at room temperature and up to 90% relative humidity. Structural degradation of the materials after regeneration is analyzed via powder X-ray diffraction (PXRD) and nitrogen adsorption measurements. MOFs with open metal sites are quite hydrophilic but appear to maintain their structure according to PXRD. However, significant surface area loss indicates that decomposition is occurring and is likely an attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
451
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(494 citation statements)
references
References 48 publications
41
451
2
Order By: Relevance
“…The structural degradation of the materials was analyzed by N 2 adsorption measurements, and we found that the MOF integrity was lost for UiO67-NH 2 (100) (Figure S10). [16] For Zr(NDC)(NDC-NH 2 ), we chose UiO67-NH 2 (20) as the starting material to introduce transition-metal complexes in the structure, by postsynthesis treatment. This material was characterized by elemental analysis, NMR and FTIR spectroscopy, and thermal analysis, and the results are given in Figures S3, S4, and S9.…”
Section: Resultsmentioning
confidence: 99%
“…The structural degradation of the materials was analyzed by N 2 adsorption measurements, and we found that the MOF integrity was lost for UiO67-NH 2 (100) (Figure S10). [16] For Zr(NDC)(NDC-NH 2 ), we chose UiO67-NH 2 (20) as the starting material to introduce transition-metal complexes in the structure, by postsynthesis treatment. This material was characterized by elemental analysis, NMR and FTIR spectroscopy, and thermal analysis, and the results are given in Figures S3, S4, and S9.…”
Section: Resultsmentioning
confidence: 99%
“…N 2 , CO 2 ) deteriorates significantly upon exposure to water vapor. [28][29][30][31][32] Upon hydration, gas sorption measurements show that MOF-74 compounds lose a substantial fraction of their original gas uptake capacity (N 2 , CO 2 ) even at 9% relative humidity and with subsequent thermal regeneration to remove adsorbed water molecules. These results point to an irreversible reaction within MOF-74, but X-ray diffraction measurements and infrared spectroscopy have not been able to detect a notable structural change or chemical transformation following hydration and thermal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Moreover, N-rich MOFs and COPs will yield N-doped porous carbons, which can enhance the properties of porous carbons, for example, N-doped or O-doped carbons may provide faradaic pseudocapacitance, improving specific capacitance of electrode materials. 27,28 MOFs, especially like zeolitic imidazolate frameworks (ZIFs) and MOF-5 have shown unusual potential to develop highly porous carbons as electrode materials in EDLCs.…”
Section: Introductionmentioning
confidence: 99%